A Systematic Review and Network Meta-Analysis to Evaluate the Comparative Efficacy of Interventions for Unfit Patients with Chronic Lymphocytic Leukemia. Issue 10 (October 2016) - Städler, Nicolas; Shang, Aijing; Bosch, Francesc; Briggs, Andrew; Goede, Valentin; Berthier, Aurelien; Renaudin, Corinne; Leblond, Veronique
Abstract Introduction Rituximab plus fludarabine and cyclophosphamide (RFC) is the standard of care for fit patients with untreated chronic lymphocytic leukemia (CLL); however, its use is limited in 'unfit' (co-morbid and/or full-dose F-ineligible) patients due to its toxicity profile. We conducted a systematic review and Bayesian network meta-analysis (NMA) to determine the relative efficacy of commercially available interventions for the first-line treatment of unfit CLL patients. Methods For inclusion in the NMA, studies had to be linked via common treatment comparators, report progression-free survival (PFS), and/or overall survival (OS), and meet at least one of the five inclusion criteria: median cumulative illness score >6, median creatinine clearance ≤70 mL/min, existing co-morbidities, median age ≥70 years, and no full-dose F in the comparator arm. A manual review, validated by external experts, of all studies that met at least one of these criteria was also performed to confirm that they evaluated first-line therapeutic options for unfit patients with CLL. Results In unfit patients, the main NMA (five studies for PFS and four for OS) demonstrated clear preference in terms of PFS for obinutuzumab + chlorambucil (G-Clb) versus rituximab + chlorambucil (R-Clb), ofatumumab + chlorambucil (O-Clb), fludarabine and chlorambucil (median hazard ratios [HRs] 0.43, 0.33, 0.20, and 0.19, respectively), and a trend for better efficacy versus rituximab + bendamustine (R-Benda) and RFC-Lite (median HR 0.81 and 0.88, respectively). OS results were generally consistent with PFS data, (median HR 0.48, 0.53, and 0.81, respectively) for G-Clb versus Clb, O-Clb, and R-Clb 0.35 and 0.81 versus F and R-Benda, respectively); however, the OS findings were associated with higher uncertainty. Treatment ranking reflected improved PFS and OS with G-Clb over other treatment strategies (median rank of one for both endpoints). Conclusion G-Clb is likely to show superior efficacy to other treatment options selected in our NMA for unfit treatment-naïve patients with CLL. Funding F. Hoffmann-La Roche Ltd.